Exploring the Dynamic Interrelationship among Money Supply, Economic Output,and Price Levels: A Comprehensive Time Series Causality Analysis in the Contextof Pakistan - Shaukat, Pinky; Bano, Bushra; Ali, Hina; Lodhi, Muhammad Talha; Nazir, Qudsia (ACADEMIA International Journal for Social Sciences, 2025)
In Pakistan, the money supply, output, and price level have a tenuous relationship, as this study has shown. Data from time series is used to encompass the years 1980-2025. This study used the Granger causality analysis, the Augmented Dickey Fuller, the Johansen co integration test, and the unit root to check for stationary to analyze the causative link. Money supply and price were considered independent variables in the study, with the GDPG serving as the dependent variable. The findings demonstrated a positive correlation between the dependent and independent variables, indicating that rising inflation and broad money will boost GDP growth or that there is a Univariate causal relationship between price and GDP growth but no evidence of any causality between prices in Pakistan. The research suggests expansionary monetary policy with higher inflation necessary and sufficient conditions for the growth of Pakistan during the study period. More work is inevitable with including some other variables and with different techniques.